Variants in the fetal genome near pro-inflammatory cytokine genes on 2q13 associate with gestational duration - Xueping Liu; Dorte Helenius; Line Skotte; Robin N. Beaumont; Matthias Wielscher; Frank Geller; Julius Juodakis; Anubha Mahajan; Jonathan P. Bradfield; Frederick T.J. Lin; Suzanne Vogelezang; Mariona Bustamante; et al. (NATURE PUBLISHING GROUP, 2022)
The duration of pregnancy is influenced by fetal and maternal genetic and non-genetic factors. Here we report a fetal genome-wide association meta-analysis of gestational duration, and early preterm, preterm, and postterm birth in 84,689 infants. One locus on chromosome 2q13 is associated with gestational duration; the association is replicated in 9,291 additional infants (combined P= 3.96 x 10(-14)). Analysis of 15,588 mother-child pairs shows that the association is driven by fetal rather than maternal genotype. Functional experiments show that the lead SNP, rs7594852, alters the binding of the HIC1 transcriptional repressor. Genes at the locus include several interleukin 1 family members with roles in pro-inflammatory pathways that are central to the process of parturition. Further understanding of the underlying mechanisms will be of great public health importance, since giving birth either before or after the window of term gestation is associated with increased morbidity and mortality.